Effects of Electromagnetic Fields on Mammalian Cells - Md Kamal Hosain (Institute of Advanced Engineering and Science, 2012)
The characteristics of mammalian cells can be influenced by electromagnetic fields (EMFs). The electromagnetic fields have a number of physiological effects on cells and tissues such as alteration of gene expression, cells viability, proliferation, apoptosis, number of mammospheres, cells cycle phase, and invasion. The existing literature proves that the impact of EMFs on mammalian cells depends on the density and uniformity of the field, frequency range, exposure time, cell types, culture environment, and culcuremedium. This paper presents a review of the impacts of EMFs on mammalian cells in vitro culture. In this article, we reviewed the contemporary understanding of the various form of electromagnetic radiation effect on cultured mammalian cells in vitro, EMF exposing systems, and internal field mechanism in the cells.DOI:http://dx.doi.org/10.11591/ijece.v2i2.269